2020
DOI: 10.1108/rbf-03-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian residential mortgage loan default: a micro-level analysis

Abstract: PurposeThis study investigates factors contributing to residential mortgage loans default by utilizing a unique dataset of borrowers' default data from one of the pioneer lending institutions in Malaysia that provides home financing to the public. Studies on mortgage loan default have been extensively examined, but limited studies utilize the individual borrower's data, as financial institutions generally hesitant to reveal their cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(148 reference statements)
2
3
0
Order By: Relevance
“…Notice that the positive sign of the logistic coefficient indicates that the higher the x i value, the higher the probability of default and vice versa. Therefore, the male is more likely to default as compared to the female, which is similar to the finding of Lin et al (2017), Chamboko and Bravo (2019), Adzis et al (2020), and Saha et al (2021). Adzis et al (2020) recommended that the Malaysian lenders may create a new mortgage loan product specifically for female borrowers since women are more responsible in their loan repayment rather than male.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Notice that the positive sign of the logistic coefficient indicates that the higher the x i value, the higher the probability of default and vice versa. Therefore, the male is more likely to default as compared to the female, which is similar to the finding of Lin et al (2017), Chamboko and Bravo (2019), Adzis et al (2020), and Saha et al (2021). Adzis et al (2020) recommended that the Malaysian lenders may create a new mortgage loan product specifically for female borrowers since women are more responsible in their loan repayment rather than male.…”
Section: Resultssupporting
confidence: 70%
“…Therefore, the male is more likely to default as compared to the female, which is similar to the finding of Lin et al (2017), Chamboko and Bravo (2019), Adzis et al (2020), and Saha et al (2021). Adzis et al (2020) recommended that the Malaysian lenders may create a new mortgage loan product specifically for female borrowers since women are more responsible in their loan repayment rather than male. Besides, we can conclude that the credit score of the tenant decreases when the tenant’s number of months late payment, the expense-to-income ratio, or age increases.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…-------------- ------------------------ -----------------Total Equity Ratio 9 Earnings Growth Variance between income at t period with income at t-1 period (EBITt -EBITt-1) EG = - -------------------------- Analysis technique applied was binary logistic regression because independent variable in this study was a dichotomous variable consisting of two nonmetric (dummy) categories (Gregova et al, 2020). A logistic model is more effective than a probability model based on linear regression since it can accommodate both qualitative and quantitative inputs (Adzis et al, 2020). The logistic regression equation models in this study were:…”
Section: Methodsmentioning
confidence: 99%
“…Yusof et al (2018) provided evidence of the effect of macroeconomic shocks on the short-and long-run effects of home financing offered by Islamic and conventional banks. Moreover, Adzis et al (2021) demonstrated interest rates as a significant determinant of mortgage loan default. Lo et al (2022) discussed the importance of monetary supply, stock market, and foreign exchange markets for housing price to rent ratios in the UK.…”
Section: Literature Reviewmentioning
confidence: 99%